Psychological impact of the COVID‐19 pandemic on nursing students in the first wave: A cross‐sectional survey - Juan Roldán‐Merino; Barbara Hurtado‐Pardos; Lorena Molina‐Raya; David Bande; Irma Casas; Mariona Farrés‐Tarafa (Wiley, 2022)
Abstract Aim The aim of the study was to evaluate the psychological impact on nursing students at the end of period of confinement during the first wave of the COVID‐19 outbreak in Spain. Design A cross‐sectional study reported in line with the STROBE guidelines. Methods Nursing students were invited to complete an online questionnaire at the end of the 2019-2020 academic year using convenience sampling. The questionnaire collected data on sociodemographic factors, work, and life experiences in relation to COVID‐19, habits and lifestyle using the World Health Organization Five Well‐Being Index (WHO‐5) and the Generalized Anxiety disorder‐7 scale. Variables related to anxiety were analysed using multiple lineal regression analysis, Results The prevalence of low psychological well‐being in the 203 students was 44.3% and of anxiety 55.7%. In the multivariate analysis the variables associated with anxiety were having worked in the pandemic, having had symptoms of COVID‐19 and having been afraid of getting infected. Conclusions The levels of anxiety due to the COVID‐19 pandemic in nursing students have been high, and levels of psychological well‐being have been low. The fact of having worked during the pandemic, having had symptoms compatible with COVID‐19 or being afraid of getting infected are associated with the highest scores for anxiety. Relevance to clinical practice This study gives more evidence on the psychological impact on nursing students during the first wave of the pandemic in Spain. This can be used to design anxiety management programmes for inclusion into teaching syllabuses. It also gives arguments for the setting up of psychological and emotional support services for these students and other healthcare professionals working during the pandemic.